Building Trust With CSR In Outpatient installation of Dinda Hospital Tangerang - Tuti Ona; Mus Aida; Kemala Rita Wahidi (Penerbit Kemala Indonesia, 2020)
This study aims to analyse the significant relationship between PPA competence and hospital facilities to patient loyalty with trust as an intervening variable in the outpatient installation of Dinda Hospital Tangerang, either partially or simultaneously. The research methodology uses a quantitative approach with the path analysis method using the Structural Equation Modelling equation. The sample was taken by using purposive sampling technique. The number of respondents is 100 patients with a minimum visit of 2 (two) times. The results showed that the competence and hospital facilities with trust have a significant relationship together with patient loyalty simultaneously; Competence has a significant positive relationship to trust; Hospital facilities have a significant positive relationship to trust; Competence has a significant positive relationship directly to patient loyalty; Hospital facilities have a positive and significant relationship directly to patient loyalty; Trust has the strongest significant positive relationship to patient loyalty; The relationship between competence and patient loyalty indirectly through the intervening variable trust has a positive relationship and a significant level stronger than directly; and the relationship between hospital facilities and patient loyalty directly has a positive relationship and a significant level stronger than indirectly through the intervening variable trust. The managerial implication of this research is an increase in CSR activities to grow up customer trust.